Factors that influence the Na/K-ATPase signaling and function - Gao, Yingnyu; Xu, Yunhui; Bai, Fang; Puri, Raghav; Tian, Jiang; Liu, Jiang (Frontiers in Pharmacology, 2025)
The transmembrane Na/K-ATPase is located in the plasma membrane of all mammalian cells. It utilizes energy from ATP hydrolysis to execute its pumping function and interacts with other proteins and/or kinase molecules to execute its signaling function. Digoxin, one of the earliest identified cardiotonic steroids (CTS) that specifically binds to the Na/K-ATPase, has been widely prescribed to manage patients with cardiovascular disease (CVD) and heart failure (HF) for over 200 years. Elevated plasma levels of CTS have been observed in patients with hypertension, chronic kidney disease (CKD), CVD, and congestive HF. After extensive research efforts spanning decades, there remain unresolved disagreements regarding the various mechanisms underlying the Na/K-ATPase signaling functions. This article examines the known and controversial mechanisms that initiate the Na/K-ATPase signaling functions and their related regulatory mechanisms.